Fashion and tourism : parallel stories - Gravari-Barbas, Maria; Sabatini, Nadzeya (Tourism social science series ;, 2023)
Fashion and tourism have common structures and similarities on many fronts. Both phenomena and their operations have been through their 'mass' cycles, currently seeking alternative ways of expression and development. Both industries are also important business sectors globally. Fashion and Tourism: Parallel Stories analyzes the convergences between fashion and tourism from an academic perspective. It investigates the existing linkages between these industries, as well as how the two synergistically impact each other through real-world case studies and examples. The central hypothesis is that these two modern 'collaborative' phenomena have been reciprocally influenced for over 200 years. Each industry is a major indicator of economic and political systems, cultures, values, and imaginaries. Their parallel analysis allows the reader to better understand not only what one owes to the other, but significantly, how their parallel actions shape and reflect contemporary societies globally.